The relationship between stress, social support, and quality of life among spouses of patients at the end-of-life stage in Thailand: A correlational study - Thawonphat, Rathapon; Junda, Tiraporn; Sumdaengrit, Bualuang (Belitung Raya Publisher - Belitung Raya Foundation, 2025)
Background: Non-communicable diseases have become a leading global health challenge, with mortality rates steadily rising. Insufficient patient care can worsen chronic illness, often placing significant caregiving responsibilities on the patient’s spouse. In some cases, spouses may need to leave their jobs to provide full-time care, especially during the end-of-life stage. Spousal caregivers often face emotionally distressing circumstances while caring for their loved ones, which can lead to elevated stress levels. However, research indicates that adequate social support can improve caregivers’ quality of life, reducing some of the burdens associated with end-of-life care. Objectives: This study aimed to assess and analyze the relationships between stress, social support, and quality of life experienced by spousal caregivers in Thailand, guided by Lazarus and Folkman’s (1984) Stress and Coping Theory. Methods: A correlational descriptive study design was used. The study was conducted with 84 spouses of patients in the end-of-life stage at a university hospital between October 2021 and March 2022. Data were collected using a questionnaire covering stress, social support, and quality of life and analyzed using Pearson’s Product Moment and Spearman Rank Correlation Coefficients. Results: The majority of spouses were women aged between 31 and 83 years (Mean = 61.24, SD = 10.42). The mean stress level was 6.40 (SD = 1.62), the mean social support was 55.07 (SD = 9.06), and the mean quality of life was 94.69 (SD = 10.04). There was no significant correlation between social support and stress (r = -0.098, p = 0.373). However, stress was negatively correlated with quality of life (r = -0.299, p = 0.006), and social support was positively related to quality of life (r = 0.219, p = 0.045). Conclusion: Spousal caregivers of patients at the end-of-life stage experienced varying levels of stress, social support, and quality of life. While no significant relationship was found between social support and stress, stress negatively impacted quality of life, while higher social support was associated with improved quality of life. Healthcare providers, especially nurses, should assess and address the stress, social support, and overall well-being of spousal caregivers to enhance their quality of life.